2016
DOI: 10.18632/oncotarget.12649
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine kinase inhibitors and mesenchymal stromal cells: effects on self-renewal, commitment and functions

Abstract: The hope of selectively targeting cancer cells by therapy and eradicating definitively malignancies is based on the identification of pathways or metabolisms that clearly distinguish “normal” from “transformed” phenotypes. Some tyrosine kinase activities, specifically unregulated and potently activated in malignant cells, might represent important targets of therapy. Consequently, tyrosine kinase inhibitors (TKIs) might be thought as the “vanguard” of molecularly targeted therapy for human neoplasias. Imatinib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 213 publications
(270 reference statements)
0
10
0
Order By: Relevance
“…Indeed, MSCs bear at the cell surface several receptors that can be considered as targets for tumor cell therapy with TKi. In particular, the expression on MSC of PDGFR-β and EGFR is well established; the effects of TKi such as imatinib, nilotinib, or gefitinib in vitro have pointed out that these drugs can affect both MSC proliferation and differentiation ( 108 122 ). These effects have been recently reviewed in very detail ( 122 ).…”
Section: Targeting Msc With Anti-tumor Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, MSCs bear at the cell surface several receptors that can be considered as targets for tumor cell therapy with TKi. In particular, the expression on MSC of PDGFR-β and EGFR is well established; the effects of TKi such as imatinib, nilotinib, or gefitinib in vitro have pointed out that these drugs can affect both MSC proliferation and differentiation ( 108 122 ). These effects have been recently reviewed in very detail ( 122 ).…”
Section: Targeting Msc With Anti-tumor Drugsmentioning
confidence: 99%
“…In particular, the expression on MSC of PDGFR-β and EGFR is well established; the effects of TKi such as imatinib, nilotinib, or gefitinib in vitro have pointed out that these drugs can affect both MSC proliferation and differentiation ( 108 122 ). These effects have been recently reviewed in very detail ( 122 ). It is clear from all these findings that, as expected, TKi can exert a strong inhibition on MSC growth and function, but their effects on MSC-mediated immunosuppression have not been studied.…”
Section: Targeting Msc With Anti-tumor Drugsmentioning
confidence: 99%
“…Also, secretion of high amounts of the chemokine CXCL12 results in increased TGF-β secretion through binding to its receptor CXCR4, which in turn causes EMT, a key step in metastasis. Thus, targeting this signaling axis has shown anti-metastatic potential in vivo 210 - 214 . However, no clinically relevant data is available for the aforementioned targets and new therapeutic strategies are thus required.…”
Section: Cancer Associated Fibroblasts (Cafs)mentioning
confidence: 99%
“…Increasing evidence has shown that specific modes of metabolism play important roles in the self-renewal capacities of both healthy and transformed stem cells 14,15. LSCs demand tightly regulated metabolism since the disruption of either glycolysis or mitochondrial respiration impairs leukemogenesis 16,17.…”
Section: Introductionmentioning
confidence: 99%